Synergizing Sustainability: Integrated Demand-Supply Strategies for Resilient Retail, Transport, and Logistics Systems: JEL Classification: L91; Q56; R41; O33; M11 - Simon Suwanzy Dzreke; Semefa Elikplim Dzreke (Generasi Sains Indonesia, 2026)
Global supply chains confront existential threats from climate volatility manifest in port-crippling storms and agricultural collapse and chronic disruptions spanning pandemics to geopolitical fragmentation, exposing the fragility of efficiency-optimized models. This research pioneers integrated computational frameworks that transcend disciplinary silos to synchronize environmental sustainability with operational resilience across retail, transport, and logistics ecosystems. Multi-method analysis combining Life Cycle Assessment, Agent-Based Modelling, and policy scenario testing demonstrates that harmonized demand-supply coordination consistently outperforms isolated interventions. Synchronized demand shaping (AI-facilitated circular consumption) and regionalized supply redesign (micro-factories) reduce end-to-end emissions by 30–40%, while dynamic AI routing cuts logistics costs by 22% during severe disruptions. Integrating policy instruments like harmonized carbon accounting amplifies stakeholder ROI by 2.8× versus fragmented approaches. The framework empowers industry and policymakers to co-optimize decarbonization and disruption preparedness, transforming brittle networks into adaptive, low-carbon value chains resilient to systemic shocks a strategic imperative beyond incremental adjustment.